PENGARUH PENGALAMAN KERJA DAN KERJA SAMA TIM TERHADAP KINERJA KARYAWAN PADA RESTAURANT INTERNATIONAL AND CONVENTION HALL PEMATANGSIANTAR - Simatupang, Febriyanti; Lie, Darwin; Butarbutar, Marisi; Sisca, Sisca (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2019)
The result of this research can be concluded as follows: 1) Work experience, teamwork, and employees performance in this company are good.. 2) The result is Å¶= 8,538 + 0,475 X1 +0,292 X2, means that there are positive influence between work experience and teamwork on employees performance. 3) The correlation result of r=0,784means that there are moderately high and positive correlation between work experience, and teamwork with employees performance. The coefficient of determination R = 0,614 means that the employees performance can be explained by work ecperience and teamwork 61,4%. 4) The research hypothesis H0 is rejected, means that work experience and teamwork have positive and significant influence on employees performance at Restaurant International and Convention Hall Pematangsiantar either simultaneosly and partially.Â Keywords: Work Experience, Teamwork, and Employees PerformanceÂ